Tibial Spine Fractures: How Much Are We Missing Without Pretreatment Advanced Imaging? A Multicenter Study. Issue 13 (November 2020) - Shimberg, Jilan L.; Aoyama, Julien T.; Leska, Tomasina M.; Ganley, Theodore J.; Fabricant, Peter D.; Patel, Neeraj M.; Cruz, Aristides I.; Ellis, Henry B.; Schmale, Gregory A.; ,; Green, Daniel W.; Jagodzinski, Jason E.; et al.
Background: There is a high rate of concomitant injuries reported in pediatric patients with tibial spine fractures, ranging from 40% to 68.8%. Many tibial spine fractures are treated without initial magnetic resonance imaging (MRI). Purpose: To understand rates of concomitant injury and if the reported rates of these injuries differed among patients with and without pretreatment MRI. Study Design: Cross-sectional study; level of evidence, 3. Methods: We performed an institutional review board–approved multicenter retrospective cohort study of patients treated for tibial spine fractures between January 1, 2000, and January 31, 2019, at 10 institutions. Patients younger than 25 years of age with tibial spine fractures were included. Data were collected on patient characteristics, injury, orthopaedic history, pretreatment physical examination and imaging, and operative findings. We excluded patients with multiple trauma and individuals with additional lower extremity fractures. Patients were categorized into 2 groups: those with and those without pretreatment MRI. The incidence of reported concomitant injuries was then compared between groups. Results: There were 395 patients with a tibial spine fracture who met inclusion criteria, 139 (35%) of whom were reported to have a clinically significant concomitant injury. Characteristics and fracture patterns were similar between groups. Of patients with pretreatment MRI, 79 of 176 (45%) had an identified concomitant injury, whereas only 60 of 219 patients (27%) without pretreatment MRI had a reported concomitant injury ( P < .001). There was a higher rate of lateral meniscal tears ( P < .001) in patients with pretreatment MRI than in those without. However, there was a higher rate of soft tissue entrapment at the fracture bed ( P = .030) in patients without pretreatment MRI. Overall, 121 patients (87%) with a concomitant injury required at least 1 treatment. Conclusion: Patients with pretreatment MRI had a statistically significantly higher rate of concomitant injury identified. Pretreatment MRI should be considered in the evaluation of tibial spine fractures to improve the identification of concomitant injuries, especially in patients who may otherwise be treated nonoperatively or with closed reduction. Further studies are necessary to refine the indications for MRI in patients with tibial spine fractures, determine the characteristics of patients at highest risk of having a concomitant injury, define the sensitivity and specificity of MRI in tibial spine fractures, and investigate patient outcomes based on pretreatment MRI status.